Multicultural-Based Islamic Religious Education Learning Methods as an Effort to Prevent Social Conflict - Meyfa Rizkia Al Aswa; Annisa Fitria; Mukmin Mukmin (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze multicultural-based learning methods in Islamic Religious Education (PAI) as a preventive effort against social conflict within educational environments. Using a library research method, this study reviews various literature related to multicultural education theories, PAI learning strategies, and their relevance in fostering tolerance among diverse students. The findings indicate that multicultural based PAI learning methods such as cross cultural dialogue, case studies, collaborative learning, and the integration of religious moderation values effectively enhance students’ understanding of differences, reduce stereotypes, and promote mutual respect. Therefore, this approach plays a significant role in preventing potential social conflicts and creating a harmonious and inclusive educational atmosphere